2019
DOI: 10.3847/2041-8213/ab2ae4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Modeling of the Multi-wavelength Observations of the Luminous GRB 190114C

Abstract: Very-high-energy (VHE; ≥ 10 GeV) photons are expected from the nearest and brightest Gamma-ray bursts (GRBs). VHE photons, at energies higher than 300 GeV, were recently reported by the MAGIC collaboration for this burst. Immediately, GRB 190114C was followed up by a massive observational campaign covering a large fraction of the electromagnetic spectrum. In this paper, we obtain the LAT light curve of GRB 190114C and show that it exhibits similar features to other bright LAT-detected bursts; the first high-en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 74 publications
8
44
0
Order By: Relevance
“…Wang et al 2019 [38] model the multi-wavelength emission after ∼1ks as synchrotron radiation from the forward shock. A similar modelling is proposed by Fraija et al [39], where the early optical/X-ray emission is instead interpreted as due to the deceleration of the jet in a wind-like stratified medium. The radio (1.3-97 GHz) emission in the early phase up to ∼1ks has been interpreted as due to the emission by the transient reverse shock that marks the time during which the jet injects its energy into the shocked region [40].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Wang et al 2019 [38] model the multi-wavelength emission after ∼1ks as synchrotron radiation from the forward shock. A similar modelling is proposed by Fraija et al [39], where the early optical/X-ray emission is instead interpreted as due to the deceleration of the jet in a wind-like stratified medium. The radio (1.3-97 GHz) emission in the early phase up to ∼1ks has been interpreted as due to the emission by the transient reverse shock that marks the time during which the jet injects its energy into the shocked region [40].…”
Section: Resultssupporting
confidence: 71%
“…The radio (1.3-97 GHz) emission in the early phase up to ∼1ks has been interpreted as due to the emission by the transient reverse shock that marks the time during which the jet injects its energy into the shocked region [40]. At present two possible scenarios seem to emerge in the interpretation of the available multi-wavelength data: either emission from the reverse/forward shock component in a wind medium (where the reverse and forward shock emission dominate the early-and late-time emission, respectively) or emission dominated solely by the forward shock produced by the expansion of the outflow in a medium whose density evolves from a wind environment to an interstellar medium (ISM) with a constant number density [39].…”
Section: Resultsmentioning
confidence: 99%
“…The value of the initial bulk Lorentz factor inferred during the deceleration phase is similar to those reported by other burst detected by Fermi-LAT (Veres & Mészáros 2012). Since GRB 160509A exhibited one of the most energetic photons reported by Fermi-LAT in the second GRB catalog, it is expected that the value of the bulk Lorentz factor lies in the range of the brightest LAT-detected bursts (500Γ1000; Abdo et al 2009a;Ackermann 2010;Ackermann et al 2011;Ackermann 2013;Ackermann et al 2014;Fraija et al 2019bFraija et al , 2019c, as found in this work.…”
Section: The Bulk Lorentz Factorssupporting
confidence: 88%
“…From the conditions in GRB jets we generically expect Synchrotron Self Compton (SSC) emission. The first public claim of VHE detection of a GRB was for GRB 190114C (Mirzoyan et al 2019), which has been modeled with a SSC origin (e.g., Fraija et al 2019;Derishev and Piran 2019;Wang et al 2019). However, no analysis published so far has performed robust multi-instrument spectral analysis showing a statistical preference for a SSC origin against a base synchrotron explanation, which may also fit the data.…”
Section: Synchrotron Self Comptonmentioning
confidence: 99%